3.4k views
4 votes
What is the solution of the system. Use the substution method. 3x+2y=11, x-2=-4y

User Nahn
by
6.2k points

1 Answer

7 votes

Answer:


x=(10)/(3) and
y=(1)/(2)

Explanation:

  • To use the substitution method, we should take one of the equations, and obtain an expression for one of the variables from this equation. Let's take the first one: 3x-2y = 11. We obtain an expression for x (it could be for y as well): 3x = 11 + 2 y ⇒
    x=(11)/(3)+(2)/(3) *{y}.
  • Now, we should replace the expression obtain for x in the first equation, on the second equation, as follow

  • x-2=4y
    ((11)/(3)+(2)/(3)*{y})-2=4*{y}
  • Then rearranging terms
    (11)/(3)-2=4*{y}-(2)/(3)*{y}
  • This expression results in
    y=(1)/(2)
  • Finally, using the firs equation, in which we obtained an expression from x,
    x=(11)/(3)-(2)/(3) *{y}, we replace y=1/2 and get
    x=(11)/(3)- (2)/(3)*{(1)/(2) }, then
    x=(10)/(3)

User Countunique
by
5.8k points